PEMILIHAN SUPPLIER APEL BERBASIS GREEN PROCUREMENT DENGAN METODE AHP (Studi Kasus: Toko Malang Strudel) - Abdul Rahim; Armey Marsusvita; Sesmita Sari (AGRIBIOS, 2023)
Industrial development and consumer concern for the environment are increasing as well as the issue of environmentally sound industrial concepts. Thus forcing the industry to make adjustments to the green industry concept in each of its businesses, including procurement, which is better known as green procurement. The purpose of this study was to select apple suppliers for strudel shops in Malang using decision making, in order to find suppliers who can increase the company's competitiveness by determining the criteria and sub criteria weights based on the concept of green procurement. This research was conducted at the cake shop Strudel Malang to evaluate and select suppliers of apples based on green procurement using the AHP method. There are six criteria used, namely quality, technological capability, pollution control, environmental management, green products, and green competence. Each criterion has sub-criteria between 3 or 4 sub-criteria. The number of sub-criteria is used to determine the RI value. The RI value is used to calculate the CR value for each criterion. The results of data processing show that the highest CR value is in the technological capability criteria and the lowest CR value is in environmental management.